Emotions and performance in elite women handball - Moen, F.; Myhre, K.; Andersen, K. A.; Hrozanova, M. (The Sport Journal, 2018)
This article looks at how emotions are associated with performance in elite women handball in Norway. The results show that positive emotions such as joy (exemplified by feeling satisfied, pleased, and happy), serenity (exemplified by feeling calm, balanced, and hopeful), interest (exemplified by feeling curious, interested, and immersed) and ecstasy (exemplified by feeling exhilarated, enthusiastic, and convinced) are positively associated with subjective performance. On the other hand, negative emotions such as anger (exemplified by feeling aggressive and angry), fear (exemplified by feeling nervous and afraid), sadness (exemplified by feeling sad and depressed) and remorse (exemplified by feeling ashamed and guilty) were found to be negatively associated with subjective performance. The present results showed that joy, serenity, and remorse uniquely explained 51% of the variance in subjective performance.